PANDEMI COVID-19 SEBAGAI UPAYA PENCEGAHAN KEPAILITAN DALAM PERSPEKTIF HUKUM POSITIF DAN HUKUM ISLAM - Liza Dzulhijjah; Fahmi Fatwa Rosyadi Satria Hamdani; Asep Hakim Zakiran (Tahkim (Jurnal Peradaban dan Hukum Islam), 2021)
Experts argue that Covid-19 can be categorized as an overmacht so it can be used as a basis for business actors to renegotiate regarding delays in paying their debts to creditors. However, the policies and circumstances mentioned above are not positively proportional to the high number of companies filed for bankruptcy in the Commercial Court during the pandemic. This raises its own problems which on the one hand Covid-19 can be used as a reason for delaying debt payments, but on the other hand it does not prevent the filing of a bankruptcy application for a corporate entity. The purpose of this study is to identify and analyze Covid-19 as an overmacht in a debt agreement as an effort to prevent bankruptcy from the perspective of positive law and Islamic law. This study uses a qualitative research method with a normative juridical approach in which researchers examine theories, concepts, or legal principles related to overmacht in bankruptcy. The results of this study indicate that the overmacht caused by the Covid-19 pandemic and the implementation of Government policies related to the Covid-19 response cannot prevent debtor bankruptcy from both a positive legal perspective and Islamic law. This is closely related to the bankruptcy requirements both in the KPKPU Law and the opinion of the majority of ulama.Keywords: Covid-19, Overmacht, Bankruptcy.